2001
DOI: 10.1177/00912700122012733
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone Pharmacokinetics and Pharmacodynamics in Relation to Sex and Race

Abstract: Prednisolone pharmacokinetics (PK) and pharmacodynamics (PD) were investigated in relation to sex and race in white males, black males, white females, and black females (n = 8/group) after a single oral dose (0.27 mg/kg) of prednisone. The study consisted of baseline and prednisone phases with 32-hour sampling in each phase. Women were studied during the luteal phase of their menstrual cycle. Total and free plasma prednisolone concentrations were assayed by HPLC and ultrafiltration, and pharmacokinetic data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 42 publications
8
60
1
Order By: Relevance
“…In the literature, exposure-effect studies of prednisolone have primarily dealt with indirect, rapid effects, such as suppression of endogenous cortisol [18][19][20][21] and osteocalcin 21 and trafficking of neutrophils and T cells. 19,20 In comparison, reports on delayed or clinical correlates are scarce and with contrasting results. Ö st et al 22 found no effect of high total prednisolone concentrations on lowering early acute renal graft rejection rates or steroid side effects, although such an effect on rejection rates has been observed for high exposures of another glucocorticoid, MP.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, exposure-effect studies of prednisolone have primarily dealt with indirect, rapid effects, such as suppression of endogenous cortisol [18][19][20][21] and osteocalcin 21 and trafficking of neutrophils and T cells. 19,20 In comparison, reports on delayed or clinical correlates are scarce and with contrasting results. Ö st et al 22 found no effect of high total prednisolone concentrations on lowering early acute renal graft rejection rates or steroid side effects, although such an effect on rejection rates has been observed for high exposures of another glucocorticoid, MP.…”
Section: Discussionmentioning
confidence: 99%
“…8 The use of glucocorticoids impairs peripheral glucose uptake and increases hepatic gluconeogenesis and glycogenolysis. 9 The plasma concentrations of various corticosteroids peak at approximately 1 h and their average half-life is about 2.5 h. 9 Prednisone and methylprednisone demonstrate their peak effect on blood glucose levels at 4-8 h with duration of action up to 12-16 h but not typically for 24 h. 10,11 Dexamethasone has a more extended effect up to ⩾ 20 h. 9 Patients who receive glucocorticoids usually have normal fasting glucose levels and high postprandial levels. There is little information available on the efficacy of oral agents in glucocorticoid-induced DM.…”
Section: Pathogenesis Of Ptdmmentioning
confidence: 99%
“…Models V and VI possess the unique ability to characterize both tolerance and rebound phenomena (Sharma et al, 1998). Some examples in the literature can be found for T-cell lymphocyte trafficking by prednisolone (model V) (Magee et al, 2001), inhibition of leukocyte survival by paclitaxel (model VII) (Minami et al, 1998), and inhibition of experimentally induced tumor necrosis factor-␣ concentrations by susalimod (VII) (Gozzi et al, 1999). Whereas the basic indirect response models assume a constant steady-state baseline value in the absence of drug (R 0 ), some biomarkers may exhibit nonstationarity or a time-dependent baseline.…”
Section: Mager Et Almentioning
confidence: 99%